Missing persons : individual eschatology in twentieth century Protestant theology - MacEwan, Donald Gordon (Trinity College (Dublin, Ireland). Department of Religions and Theology, 2001)
This thesis comprises a survey and critique of individual eschatology according to the major Protestant theologians of the twentieth century; Rudolf Bultmann, Karl Barth, and the post-Barthians Jurgen Moltmann and Eberhard Jungel. Through a close reading of their writings on individual eschatology and other topics which have a strong bearing on the subject, aided by a comprehensive survey of secondary criticism, common features in their positions regarding the destiny of the individual human being in and beyond death are established.
Keywords: Religion, Ph.D.; Ph.D. Trinity College Dublin